A Novel Child Burial from Tierra del Fuego: A Preliminary Report - Prieto, Alfredo; Morano Buchner, Susana Javiera; Cardenas, Pedro; Sierpe Gonzalez, Victor Manuel; Calas, Elisa; Christensen, Marianne; Lefevre, Christine; Laroulandie, Veronique; Espinosa-Parrilla, Yolanda; Ramirez, Oscar; Lalueza-Fox, Carles; Hagelberg, Erika; et al. (My University, 2020)
This paper reports the archaeological materials from a unique child burial recently discovered in Tierra del Fuego. Preliminary analyses are consistent with the idea that the burial belongs to the Selk'nam culture. Although the Selk'nam archaeological record is abundant, very little is known about their mortuary practices. In this well-preserved burial, the human remains were accompanied by an unusual set of grave goods, which have not been described in the archaeological literature for this region. Radiocarbon dating places this burial at the beginning of the Post-Columbian period in Tierra del Fuego (331-499 cal BP). Analyses presented herein include information on the sex, diet, and genetics of the child, which provided the first genetic evidence for the presence of mitochondrial sub-haplogroup D1g5 in the Selk'nam population in Tierra de Fuego. We also provide a detailed description of the cultural materials, which include mammal and bird bones and lithic material. This is a unique find because it possesses a wealth of archaeological materials that are previously unknown in the region.
Keywords: selk'nam; burial practices; tierra del fuego; hunter-gatherers; ancient dna